Tantangan Kebijakan Pengawasan Obat dan Makanan dalam Mendukung Peningkatan Daya Saing, Ekonomi dan Bisnis di Indonesia: Sebuah Studi Analisis - Perdhana Ari Sudewo (Eruditio : Indonesia Journal of Food and Drug Safety, 2021)
In line with Indonesia's target to become a developed country by 2045, structural reforms in the industrial sector in Indonesia will continue to be carried out with a target in 2030 to be able to contribute 30% to Indonesia's Gross Domestic Product (GDP). In structural reforms, the Drug and Food Industry is a priority industry. It requires a Drug and Food Control policy issued by the Indonesian Food and Drug Authority (Indonesian FDA) to support increasing competitiveness by creating a business ecosystem that supports Indonesia's economic growth. This study aims to analyze the challenges of Drug and Food Control policies in increasing the competitiveness of the Drug and Food Industry to support economic growth, expand employment, and create a good business ecosystem in Indonesia. The study was conducted using secondary data through literature studies from books, journals, reports, study results, articles, and internal Indonesian FDA documents. The results of the study show that the Indonesian FDA must be ready and adaptive to face various supervisions, including challenges that have never been faced by the Indonesian FDA before, the impact of government demands, the digitization of the Industrial sector, and the development of Food and Drug Science. The Indonesian FDA must formulate appropriate policies and prepare adequate resources to be able to face these challenges. This study is expected to provide benefits for policymakers and employees at the Indonesian FDA and relevant stakeholders in preparing, compiling, and establishing appropriate policies to support competitiveness, economy, and business in Indonesia.